2016
DOI: 10.1111/jphp.12561
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of phenolic antioxidants in Scabiosa arenaria flowers by LC–ESI-MS/MS and NMR

Abstract: The results of the present work indicate that S. arenaria flower's ethyl acetate extract could be used as natural antioxidant agents in food preservation and human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…A debris ion at m / z 269 was examined in peak 9, and the [M − H] − was 431.0984, indicating a loss of glucoside. Therefore, peak 9 was considered to be apigenin-7-O-glucoside (apigetrin) [25]. For peak 13 (tR = 19.34 min), the molecular ion [M + H] + was seen at m / z 317.9656 in the positive mode.…”
Section: Resultsmentioning
confidence: 99%
“…A debris ion at m / z 269 was examined in peak 9, and the [M − H] − was 431.0984, indicating a loss of glucoside. Therefore, peak 9 was considered to be apigenin-7-O-glucoside (apigetrin) [25]. For peak 13 (tR = 19.34 min), the molecular ion [M + H] + was seen at m / z 317.9656 in the positive mode.…”
Section: Resultsmentioning
confidence: 99%
“…The extract of S. flavida significantly attenuated the amount of OS in the fibroblast cells almost with a power like EA. The genus Scabiosa has been enriched by phenolic constituents, in particular flavonoids, iridoids, and triterpene saponins, allowing it to possess antioxidant, anti‐inflammatory, analgesic, and many other biological actions . The antioxidant and scavenging capacity of F .…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] Many of Scabiosa species contain triterpenes, triterpene glycosides, triterpene saponins, iridoids, iridoid glucosides, monoterpenoid glucoindole alkaloids, coumarins and flavonoids. [18][19][20][21][22] It has been reported that extracts of S. tschilliensis and S. comosa, [23] S. arenaria, [24] S. tschilliensis, [25] compounds isolated from S. arenaria flowers [26] and S. comosa influorescence [27] have antioxidant property. Swerosid and seco-iridoid isolated from S. columbaria roots, [28] essential oil from fruit, stem and leaf and flowers of S. arenaria, [16] ethanol extracts of S. arenaria, [29] Lomelosia olivieri (Coult.)…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that extracts of S. tschilliensis and S. comosa , [23] S. arenaria , [24] S. tschilliensis , [25] compounds isolated from S. arenaria flowers [26] and S. comosa influorescence [27] have antioxidant property. Swerosid and seco‐iridoid isolated from S. columbaria roots, [28] essential oil from fruit, stem and leaf and flowers of S. arenaria , [16] ethanol extracts of S. arenaria , [29] Lomelosia olivieri (Coult.)…”
Section: Introductionmentioning
confidence: 99%